Germination Response and Estimation of Seed Deterioration of (Satureja hortensis) under Various Storage Conditions - saeed amini; Mohammad Hassan assarah; Abbas Dehshiri; Shahla Hashemi Fesharaki (علوم و فناوری بذر ایران)
The main goal of seed storage is to maintain its quality from harvesting to sowing time. Among all factors, storage temperature and seed moisture content are the most important factors affecting seed longevity. This experiment was conducted at University of Tehran, Department of Agronomy and Plant Breeding during 1394 to determine the Ellis and Roberts deterioration model of Satureja hortensis seeds and introduce constants of viability equation. Seed viability and initial moisture content was measured and after that seeds were adjusted to 5, 7, 9, 11 and 13% moisture content and sealed hermetically in Nano packets. Storage temperatures were 10, 15, 20 and 25˚C. The interval of sampling depended on the storage conditions. Seed viability constants were estimated to predict seed longevity in this species and relationship between sigma and moisture content and temperatures was determined. After probit analysis, survival curves were depicted in each condition. Results showed that seeds with 5% moisture content stored at 10°C had the highest germination percentage, but seeds which were stored at 13% moisture content and 20 and 25°C had the highest deterioration rate. Estimates of KE, CW, CH and CQ were 4.31, 1.83, 0.031 and 0.0004, respectively. Also, the results showed that seed longevity decrease with increased seed moisture and temperature.